Enantiopure titanocene complexes – direct evidence for paraptosis in cancer cells. Issue 3 (25th January 2016) - Cini, Melchior; Williams, Huw; Fay, Mike W.; Searle, Mark S.; Woodward, Simon; Bradshaw, Tracey D.
Abstract : Enantiopure titanocene complexes exert selective antitumour activity evoking paraptosis. HPLC, MS and NMR revealed Cp R 2 Ti(OH)(OH2 ) + as the likely trigger. Abstract : Tolerated by normal tissues, anti-cancer therapies based on titanium compounds are limited by low efficacy/selectivity and lack of understanding of their mode(s) of action. In vitro antitumour activity and mode of cell death incurred by enantiopure TiCl2 η-C5 H4 CHEt(2-MeOPh)2 (abbreviated Cp R 2 TiCl2 ) has been investigated. The in vitro anti-tumour activity of Cp R 2 TiCl2 is selective for cancer cells; in clonogenic assays, ( S, S )-Cp R 2 TiCl2 was twice as effective at inhibiting colony formation than other stereoisomers after 24 h exposure. HPLC, MS and NMR techniques determined hydrolysis of Cp R 2 TiCl2 ; data strongly correlate with soluble [Cp R 2 Ti(OH)(OH2 )] + being the biological trigger. Treatment of cells with Cp R 2 TiCl2 provoked extensive cytoplasmic vacuolization, endoplasmic reticulum (ER) swelling and activation of MAPKinase signal transduction, consistent with ligand-induced paraptosis, type III cell death, which is morphologically distinct from, and independent of apoptosis. Indeed, distinct from cisplatin, Cp R 2 TiCl2 failed to perturb cell cycle dynamics, induce γH2AX foci or evoke apoptosis in MDA-MB-468 and HCT-116 cells.